Ethics And Data Privacy: The Backbone of Trustworthy Healthcare Practices - Rakesh Margam (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
In today's rapidly evolving digital landscape, the healthcare industry has embraced data-driven technologies to enhance patient care and medical research. However, this transformation brings forth the crucial responsibility of safeguarding sensitive patient data and adhering to ethical principles. This article delves into the paramount significance of data privacy and ethics in healthcare, placing a strong emphasis on maintaining patient trust and upholding research integrity. Implementing robust security measures, including encryption and access controls, is imperative to protect patient information from unauthorised access. Ethical considerations underpin the responsible handling of patient data, emphasising the importance of obtaining informed consent and maintaining transparent communication. Striking a delicate balance between innovation and patient privacy involves leveraging privacy-preserving techniques while harnessing the potential of Artificial Intelligence (AI) and big data analytics. Empowering patients in data privacy decisions, through granting access to their health data and fostering transparent policies, further solidifies the foundations of trust in the healthcare sector. Upholding data privacy and ethics not only aligns with regulatory compliance but also embodies a moral obligation to prioritise patient dignity and foster progress in the dynamic realm of healthcare.